Contribution of Transverse Reinforcement Configuration on Concrete Shear Capacity of RC Column - Taufiq Saidi; Rudiansyah Putra; Zahra Amalia; Munawir Munawir (Aceh International Journal of Science and Technology, 2019)
Proper design of transverse reinforcement in the RC column is needed to maintain its ability to deform under axial and shear load safely. Even though mandatory building codes for transverse support of the RC column exist, shear failure was still found in the last high earthquake in Pidie, Aceh, in 2016. Therefore, as an attempt to improve RC column strength and elasticity, the effect of transverse reinforcement configuration was evaluated experimentally to a column subjected to an axial and shear load. The experiment was conducted by using four-column specimens with a cross-section 200 x 200 mm. Four types of transverse reinforcement configurations were applied in each column. The test was carried out by loading an axial load always and shear load gradually until its failure. The test results show that the configuration of transverse reinforcement has a significant effect of maintaining column stiffness, which was subjected to compressive axial load and shear load. Furthermore, the arrangement of transverse reinforcement influences the compressive strength significantly and enhance the concrete shear capacity of a column due to its confinement effect.